Influence of radiotherapy on cardiac implantable device lead parameters. (3rd October 2022) - Warmbrunn, J; Straube, C; Haase, H U; Sinnecker, D; Laugwitz, K L; Combs, S E; Schneider, S; Habermehl, D
Abstract: Purpose: Incidences of both cardiac implantable electronic devices (CIED) and malignant tumors are rising, likewise the number of patients undergoing radiotherapy (RT) while having CIED increases. There is evidence that there is a higher failure rate with increasing cumulative dose at device and higher – neutron-inducing – photon beam energy above 10 MV. There is a paucity of data regarding lead function, lead insertion site dose and analysis of change of lead parameter during RT treatment. Aim of this work is a detailed analysis of CIED malfunctions and technical alterations in patients treated at our clinic with a special focus on device lead parameters. Methods: In a total of 54 patients treated at our department, we evaluated the dose statistics for the leads and devices as well as lead parameters aggregated through telemetric device interrogations. Irradiation mostly took place in the thoracic (32%), pelvic (24%) and the head region (22%). A total of 80% of all patients had implanted a pacemaker and 17% an implantable cardioverter defibrillator. Two Patients (4%) were under cardiac resynchronization therapy. Overall 33% of patients were device-dependent. Dose statistics for myocardial lead insertion sites and CIED were calculated. We collected interrogation data (intrinsic pacing impedance, pacing threshold, signal amplitude) before and after RT treatment (median number of interrogations was 3, range 1–22) and information about any CIED malfunction. We assessed whether lead parameters changes exceeded predefined thresholds of 30% in pacing impedance, 50% in pacing threshold, or 50% in signal amplitude. Results: 24 of the 54 patients received a measurable dose at the device (median dose of patients with thoracic RT: 1.82 Gy, range 0.18–14.88 Gy). Dose data was available for atrial leads of 12 patients (median dose 7.27 Gy, ranging from barely measurable to 46.02 Gy) and right-ventricular leads of 13 patients (median dose 0.83 Gy, range 0.004–42.66 Gy). There was no lead parameter threshold violation for pacing impedance detected, however predefined thresholds of signal amplitude and pacing threshold were exceeded in 14% and 15% of cases, respectively. These threshold violations did not compromise device function. There was no significant difference of lead parameter changes when patient groups receiving more and less than 10 Gy at lead insertion site were compared. Two CIEDs (4%) showed a malfunction (electric restart of device) during RT, however no clinically relevant complication was reported. Both patients underwent thoracic RT (esophageal cancer) with a beam energy of 10 and 15 MV. Conclusion: In the observed patient group, lead parameter threshold violation was neither able to predict a device malfunction nor dependent of cumulative dose at myocardial insertion side. Device malfunction occurred rarely and only at higher beam energies, however with no life-threatening outcome. Funding Acknowledgement: Type of funding sources: None.